1 Answer | Add Yours
Plugging y = 0 in the relation yields: `f(x)<= f(0)`
Replacing y by `-sqrtx ` and x by `sqrt x` yields: `f(sqrtx - sqrtx) = f(0)<= f(-x)=gt f(-x) = 0.`
Replacing y by `-sqrtx` and x by `-sqrt x` yields: `f(0) = f(sqrtx+sqrtx) = f(0)<= f((-sqrtx)*(-sqrtx)) = f(x) =gt f(x) = 0` .
If f(x) = f(0) => the function is constant.
The conclusion to this study is that only the constant functions, f(x) = a, check the relation `f(x+y) <=f(xy).`
We’ve answered 320,034 questions. We can answer yours, too.Ask a question